Sustainable Development of Language Communication: Localization and Innovation of Confucius Institutes in Spain - Qiuyang, Li (Sinología hispánica. China Studies Review, 2024)
Confucius Institute has fulfilled its function of spreading of Chinese language around the world since it was founded in 2004. Localization of teaching process towards regional educational and cultural system becomes key important for the sustainability of CI overseas. This paper adopts qualitative methodology of in-depth interviews among 18 participants who are administrative and teaching staff in the CIs of Spain to investigate the characteristic motivation, path, mode and effectiveness of CI in order to seek new ways to solve the problems of regional positioning, integrative strategy and post-pandemic development from the perspective of country-specificity and localization for the cross-border education. The findings of this study show that the CIs in Spain promote cross-fertilization between Chinese and Spanish teachers, share core values tactically via transnational culture and strengthen a positive cognition among local media and learners. In order to achieve the depth and breadth of the localization of Chinese education in Spain, the following strategies should be adopted: Targeting the economic and cultural values of Chinese language, investigating the local language policies in depth, and promoting the full integration of Chinese into the Spanish national education system; formulating the adaptive strategies for the localization of international Chinese level standards to increase the supply of Chinese teaching resources; understanding the current situation of teacher training in Chinese education in Spain and assisting the local teacher training at all levels; improving the ability of international Chinese education precision service.